1982
DOI: 10.1017/s0003356100027355
|View full text |Cite
|
Sign up to set email alerts
|

The effect of birth weight on the estimated milk intake, growth and body composition of sow-reared piglets

Abstract: Ten littermate pairs were used to study the effects of light and heavy birth weight on the development of muscle tissue, growth rate, body composition and the estimated milk consumption of piglets reared on the sow to 6·5 kg live weight.Neither average daily gain to 6·5 kg nor body composition at the latter weight were significantly affected by birth weight. Birth weight also had no effect on the weight or deoxyribonucleic acid content of the semitendinosus musde at 6·5kg. However, pigs of hght birth weight -w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0

Year Published

1986
1986
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(26 citation statements)
references
References 12 publications
1
25
0
Order By: Relevance
“…Birth weight in pigs has been linked to differences in both growth rate and body composition. Low birth weight pigs exhibit a 15 % to 30 % lower growth rate (compared to medium and high birth weight pigs) in the 1st month of postnatal life (Campbell & Dunkin 1982, Wolter et al 2002, Poore & Fowden 2004, Gondret et al 2005, Škorjanc et al 2007. Based on chemical analysis of the whole body at birth, Rehfeldt & Kuhn (2006) reported that low birth weight pigs have less fat and protein and more water than their littermates.…”
Section: Resultsmentioning
confidence: 99%
“…Birth weight in pigs has been linked to differences in both growth rate and body composition. Low birth weight pigs exhibit a 15 % to 30 % lower growth rate (compared to medium and high birth weight pigs) in the 1st month of postnatal life (Campbell & Dunkin 1982, Wolter et al 2002, Poore & Fowden 2004, Gondret et al 2005, Škorjanc et al 2007. Based on chemical analysis of the whole body at birth, Rehfeldt & Kuhn (2006) reported that low birth weight pigs have less fat and protein and more water than their littermates.…”
Section: Resultsmentioning
confidence: 99%
“…Weaning weight is positively correlated to birth weight with LBW piglets still exhibiting a lower BW at weaning than their counterparts with a MBW (equivalent to the mean litter BW) or a HBW (more than 1.9 kg). Compared with MBW or HBW piglets, LBW piglets exhibit a lower growth rate (15% to 30%) in the 1st month of postnatal life (Campbell and Dunkin, 1982;Wolter et al, 2002;Poore and Fowden, 2004a;Gondret et al, 2005 and. During the first 3 weeks of suckling, it has been shown that milk intake per unit BW is similar in the two groups even though LBW piglets consume less milk per suckle than MBW piglets (Campbell and Dunkin, 1982).…”
Section: Growth In Low Birth Weight Pigletsmentioning
confidence: 99%
“…Compared with MBW or HBW piglets, LBW piglets exhibit a lower growth rate (15% to 30%) in the 1st month of postnatal life (Campbell and Dunkin, 1982;Wolter et al, 2002;Poore and Fowden, 2004a;Gondret et al, 2005 and. During the first 3 weeks of suckling, it has been shown that milk intake per unit BW is similar in the two groups even though LBW piglets consume less milk per suckle than MBW piglets (Campbell and Dunkin, 1982). The higher birth weight piglets tend to select the anterior teats (Hartsock et al, 1977) that are easier for milk extraction.…”
Section: Growth In Low Birth Weight Pigletsmentioning
confidence: 99%
“…These may both contribute to the reduced birth weight and poorer subsequent performance of progeny of primiparous pigs (first pregnancy, gilts) compared with multiparous pigs (sows), since fetal growth and birth weight predict neonatal survival and postnatal growth and metabolism in pigs, as in other species (Winters et al 1947, Fahmy & Bernard 1971, Campbell & Dunkin 1982, Wigmore & Stickland 1983, Dwyer et al 1993. Multiple factors can restrict fetal growth and birth weight in pigs; competing maternal demands in growing adolescent animals, large and variable litter size, and restricted maternal nutrition used in commercial pig production systems during pregnancy.…”
Section: Introductionmentioning
confidence: 99%